Manajemen Kurikulum Untuk Meningkatkan Mutu Pendidikan Islam (Studi kasus di SMA Plus Nurul Ulum) - Khadavi, Muammar (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Curriculum management is a crucial aspect in determining the direction and quality of education in an institution. The quality of Islamic education is reflected in the success of the institution in producing graduates who are in accordance with the goals that have been set. This study aims to describe curriculum management in improving the quality of Islamic education in SMA Plus Nurul Ulum. This study uses a qualitative approach with a case study type. Data collection techniques are carried out through observation, interviews, and documentation, while data analysis uses the stages of data reduction, data presentation, and verification. The results of the study indicate that curriculum management in SMA Plus Nurul Ulum is implemented through three main stages. First, curriculum planning is carried out through a core team meeting involving the principal, vice principal, teachers, and supervisors, to compile and socialize learning tools. Second, curriculum implementation is carried out through checking teacher readiness, evaluating performance every three months, instilling Islamic values, and training through In House Training (IHT). Third, curriculum evaluation includes allocating special time to evaluate learning tools and teacher performance. Overall, curriculum management in SMA Plus Nurul Ulum has been carried out systematically and has contributed significantly to improving the quality of Islamic education.